Clinical and economic impact of the 21-gene recurrence score assay in adjuvant therapy decision making in patients with early-stage breast cancer: pooled analysis in 4 Basque Country university hospitals - Martínez del Prado P; Alvarez-López I; Domínguez-Fernández S; Plazaola A; Ibarrondo O; Galve-Calvo E; Ancizar-Lizarraga N; Gutierrez-Toribio M; Lahuerta-Martínez A; Mar J (Dove Medical Press, 2018)
Purificación Martínez del Prado,1 Isabel Alvarez-López,2,3 Severina Domínguez-Fernández,4 Arrate Plazaola,5 Oliver Ibarrondo,6 Elena Galve-Calvo,1 Nerea Ancizar-Lizarraga,2,3 María Gutierrez-Toribio,4 Ainhara Lahuerta-Martínez,5 Javier Mar6,7 1Medical Oncology Service, Basurto University Hospital, Bilbao, Spain; 2Medical Oncology Service, Donostia University Hospital, Donostia-San Sebastián, Spain; 3Biodonostia Health Research Institute, Donostia-San Sebastián, Spain; 4Medical Oncology Service, Araba University Hospital, Vitoria-Gasteiz, Spain; 5Medical Oncology Service, Onkologikoa, Donostia-San Sebastián, Spain; 6AP-OSI Research Unit, Alto Deba Integrated Health Care Organization, Mondragon, Spain; 7Health Services Research on Chronic Patients Network, Kronikgune Group, Bilbao, Spain Purpose: The 21-gene recurrence score (RS) is a genomic test developed as a prognostic and predictive tool to improve the treatment decision making in cases of estrogen receptor-positive and human epidermal growth factor receptor 2-negative early-stage breast cancer. This study examined the clinical and economic impact of its use in 4 Basque Country university hospitals. Methods: Taking into consideration the RS result, we recorded the recommended initial systemic adjuvant therapy (endocrine therapy with or without chemotherapy) according to standard clinicopathologic factors and the final decision about chemotherapy. Then, if the RS was high, chemotherapy was recommended; it was not recommended if the RS was low; for those with an intermediate RS, clinicopathologic factors were considered, and the initial recommendation based on those factors was maintained. In addition, the probability of switching treatment was calculated. Then, we developed an economic evaluation by measuring the treatment’s incremental short-term budget impact from both the societal perspective and that of the Basque Health System. Patients’ characteristics and chemotherapy use were analyzed using logistic regressions and receiver operating characteristic curves. Results: Without an RS, chemotherapy would have been prescribed to 56% of 401 patients, but, with RS use, that percentage decreased to 25. The overall rate of decision change was 35.4%. Test inclusion led to a reduction in chemotherapy costs of €922 per patient in the total population. Although this reduction did not entirely offset the cost of the test, the productivity loss per patient was reduced by €1,977. Conclusion: The 21-gene RS test significantly changed the indication for chemotherapy. As chemotherapy treatments with no benefit were avoided, patients’ quality of life was improved. The short-term economic impact was negative for the Basque Health Service, but savings resulted when sick-leave costs were included. Keywords: early-stage breast cancer, adjuvant chemotherapy, 21-gene assay, economic evaluation, health care costs